Response to chemotherapy against mediastinal lymphoma in a domestic cat - Hinostroza M, Elizabeth. (2018)
It is reported the treatment of a 2-year-old male castrated domestic feline, 6.8 kg of body weight, with mediastinal lymphoma. At clinical examination, it showed a temperature of 38 °C, superficial restrictive inspiratory dyspnea, <2 s capillary refill time, heart rate of 140 beats/min, respiratory rate 62/min. In the laboratory analyzes was found leukopenia with lymphopenia and positive for the feline leukemia virus. Radiography and thoracic ultrasound showed moderate pleural effusion and a rounded hypoechoic structure with irregular edges, respectively. The thoracocentesis revealed the presence of chylothorax and the cytology by fine needle puncture of the rounded structure allowed a final diagnosis of mediastinal lymphoma. A chemotherapy was instituted with L-asparaginase, vincristine, cyclophosphamide, doxorubicin, and prednisolone. The patient underwent eight chemotherapy sessions until, due to toxicity reactions, it was decided to suspend them. During the treatment period, a partial remission of the tumor, a significant decrease in the effusion and an improvement in the quality of life of the patient were achieved. The main adverse effect was myelosuppression. An approximate survival time of more than 120 days was reached.